Osteoarthritis develops in the operated joint of an ovine model following ACL reconstruction with immediate anatomic reattachment of the native ACL. Issue 1 (13th July 2012) - O'Brien, Etienne J.O.; Beveridge, Jillian E.; Huebner, Kyla D.; Heard, Bryan J.; Tapper, Janet E.; Shrive, Nigel G.; Frank, Cyril B.
Abstract We tested the hypothesis that immediate reattachment of the native anterior cruciate ligament (ACL) can prevent kinematic changes and the development of osteoarthritis (OA). Five sheep underwent anatomic unilateral ACL reconstruction (ACL‐R). Animals from a previous study served as sham (n = 7) or non‐operated (n = 17) controls. At 4 points of walking gait, 6 degrees of freedom stifle joint kinematics of ACL‐R animals were compared with sham controls at 4 and 20 weeks post‐surgery. Gross cartilage, bone, and meniscal changes were graded at euthanasia; paired and differential scores were compared. Inter‐animal differences were noted in all groups. Of 48 points of gait comparison between ACL‐R and sham operated groups, 42 points showed no difference (p > 0.05). Of the six significant differences (p < 0.05), internal rotation in ACL‐R animals accounted for three. At 20 weeks, differential scores showed that sham operated joints were morphologically indistinguishable from non‐operated controls (p ≥ 0.129) while ACL‐R joints had significantly higher combined cartilage and osteophyte scores than those controls (p ≤ 0.003). This method of ACL reconstruction in sheep did not restore normal walking gait kinematics completely and allowed some OA to develop in operated joints. OA may result from relatively subtle mechanical abnormalities, apparently more so in some individuals than others. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:35–43, 2012